Dual-Confined and Hierarchical-Porous Graphene/C/SiO2 Hollow Microspheres through Spray Drying Approach for Lithium-Sulfur Batteries. (20th November 2017) - Wu, Huali; Tang, Qunli; Fan, Haining; Liu, Zheng; Hu, Aiping; Zhang, Shiying; Deng, Weina; Chen, Xiaohua
Graphical abstract: An integrated structure of dual-confined and hierarchical-porous Graphene/C/SiO2 hollow microspheres are synthesized by simply spray drying and carbonization process with the help of melt-diffusion. The as-synthesized S-G/C/SiO2 composite display greatly improved performance in comparison with S-G/C. Highlights: The G/C/SiO2 microspheres could effectively imprison the polysulfide via physical adsorption and chemical binding. The G/C/SiO2 microspheres with appropriate SiO2 content facilitate to form optimized micro-meso-macro porous structure. The S-G/C/SiO2 with 20.1 wt. % SiO2 exhibits high rate capability and cycling stability. Abstract: Rational robust hierarchical-porous Graphene/C/SiO2 hollow microspheres (G/C/SiO2 ) were designed as scaffold to load sulfur. The sulfur was impregnated into the microspheres to generate sulfur-Graphene/C/SiO2 composites (S-G/C/SiO2 ) for Li-S batteries. The 3D porous microspheres consist of SiO2 nanoparticles connected by interconnected graphene and carbon layer, which could leave enough room for volume changes of sulfur during the charge-discharge process, and imprison the polysulfide via physical adsorption and chemical binding, thus effectively improving the cycle stability. As a result, the S-G/C/SiO2 with 20.1 wt. % SiO2 exhibits high discharge capacities up to 1118.4 mA h g −1 at 0.1C, an excellent rate capability of 551.7 mA h g −1 at 5C, and an exciting cycle performance of 626.3 mA h g −1 after 400 cycles at 0.5C (ultralow capacity decay of only 0.062% per cycle), represented to be a promising cathode material for Li-S batteries.